The Effect Of Work Discipline On Employee Performance At The Binjai City Regional Inspectorate Office - Inggit Gemiasih; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2024)
This study was a quantitative associative causal research aimed at analyzing the relationship pattern between variables and determining the influence of two independent variables (exogenous) on the dependent variable. The research was conducted at the Secretariat Office of Binjai City, with apopulation of 68 employees. The sampling technique used is saturated sampling, which is a technique where all members of the population are selected as samples. The data used in this study were obtained from questionnaires distributed to respondents consisting of all employees from various divisions. The results showed that Work Discipline has a positive and significant effect on Employee Performance. This is evidenced by the t-count value of 20.338 > t-table value of 1.99656, with a significance value of 0.000 < 0.05. The regression coefficient of 1.852 indicates that for every 1-point increase in Work Discipline, Employee Performance will increase by 1.852 points, assuming other variables remained constant. Additionally, the coefficient of determination test results show an Adjusted R Square value of 0.862 or 86.20%, indicating that Work Discipline had a very high impact on Employee Performance, with the remaining 13.80% influenced by other factors not examined in this study. Overall, the results of this study identified that improving work discipline could contribute to enhancing employee performance at the Secretariat Office of Binjai City.